Detection of Metastatic Disease in Cardiophrenic Lymph Nodes: FDG PET/CT Versus Contrast-Enhanced CT and Implications for Staging and Treatment of Disease - Farmakis, Shannon; Vejdani, Kaveh; Muzaffar, Razi; Parkar, Nadeem; Osman, Medhat M. (Frontiers in Oncology, 2013)
Objective: To determine whether FDG PET/CT was more sensitive than CT in detecting metastatic disease in the cardiophrenic space and whether the presence of disease in this location would change the staging and clinical management. Materials and Methods: About 1200 PET/CT scans were retrospectively reviewed over 20 months for the presence of FDG-avid cardiophrenic lymph nodes. The SUVmax was used to quantify the metabolic activity in each of the lymph nodes. The radiographic data was used for correlation. A retrospective review of diagnostic CT reports performed within a 1-month period of time of the PET/CT in the same subset of patients determined whether cardiophrenic lymph nodes were mentioned. Results: About 9 (0.8%) of the 1200 studies were found to have FDG-avid cardiophrenic lymph nodes (four males and five females with a mean age of 55 years; range 7–69, median 59). The mean SUVmax was 2.4 (range 1.2–7.9; median 1.9). Only three of the patients were found to have suspicious lymph nodes on CT. The presence of cardiophrenic lymph nodes had the potential to change the staging and/or management in three of the patients. Conclusion: PET/CT is more accurate in the detection of pathologic cardiophrenic lymph nodes than CT, especially when they are subcentimeter in size. When present, staging and/or management was potentially affected in 33%. Therefore, these nodes should be included in the TNM staging classification.